1996
DOI: 10.1038/382810a0
|View full text |Cite
|
Sign up to set email alerts
|

A diffusible coupling signal from the transplanted suprachiasmatic nucleus controlling circadian locomotor rhythms

Abstract: The mammalian suprachiasmatic nuclei (SCN) transmit signals to the rest of the brain, organizing circadian rhythms throughout the body. Transplants of the SCN restore circadian activity rhythms to animals whose own SCN have been ablated. The nature of the coupling signal from the grafted SCN to the host brain is not known, although it has been presumed that functional recovery requires re-establishment of appropriate synaptic connections. We have isolated SCN tissue from hamsters within a semipermeable polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
386
0
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 720 publications
(395 citation statements)
references
References 20 publications
5
386
0
4
Order By: Relevance
“…As mentioned previously, these grafts restore activity-related behaviors such as locomotor, drinking, and gnawing rhythms (Lehman et al, 1987;Ralph et al, 1990;Silver et al, 1990). That a diffusible signal is sufficient to restore locomotor rhythmicity in SCN-lesioned hosts was demonstrated by encapsulating donor SCN tissue in a membrane that prevented neural outgrowth while allowing the diffusion of signals between graft and host (Silver et al, 1996).…”
Section: Circadian Output and Orchestration Of Endocrine Function Difmentioning
confidence: 80%
See 1 more Smart Citation
“…As mentioned previously, these grafts restore activity-related behaviors such as locomotor, drinking, and gnawing rhythms (Lehman et al, 1987;Ralph et al, 1990;Silver et al, 1990). That a diffusible signal is sufficient to restore locomotor rhythmicity in SCN-lesioned hosts was demonstrated by encapsulating donor SCN tissue in a membrane that prevented neural outgrowth while allowing the diffusion of signals between graft and host (Silver et al, 1996).…”
Section: Circadian Output and Orchestration Of Endocrine Function Difmentioning
confidence: 80%
“…In contrast to behavioral rhythms (e.g., locomotion, drinking, gnawing), endocrine rhythms require neural projections from the SCN to endocrine targets; endocrine rhythms are abolished after knife cuts severing SCN efferents (Hakim et al, 1991;Nunez and Stephan, 1977) and are not restored in SCN-lesioned transplanted animals (Meyer-Bernstein et al, 1999;Nunez and Stephan, 1977;Silver et al, 1996), presumably due to inadequate neural innervation of the host brain by the graft. Further evidence for a neural SCN output signal regulating hormone secretion is seen in studies of female hamsters.…”
Section: Neural Control Of Neurosecretory Factorsmentioning
confidence: 99%
“…This suggests that the photoperiodic differences in fever duration between LD and SD reported here and elsewhere (Bilbo and Nelson, 2002;Bilbo et al, 2002b) may be due in part to entrainment of the circadian rhythm in body temperature. Given that the generation of circadian rhythms in the periphery is driven by the neural and humoral output of the SCN (Silver et al, 1996;Meyer-Bernstein et al, 1999;Kramer et al, 2001), and is almost entirely independent of any reciprocal influence by the pineal gland or melatonin (Sumova and Illnerova, 1996;Prendergast and Freeman, 1999), PINx would be expected to have little effect on photoperiodic differences in the febrile response to LPS if such differences are due solely to circadian factors.…”
Section: Discussionmentioning
confidence: 99%
“…The endogenous biological clock that controls mammalian circadian rhythms is located in the suprachiasmatic nuclei of the anterior hypothalamus and regulates a wide variety of circadian rhythms in behavior, autonomic function, and neuroendocrine physiology (27). Fetal grafts of the SCN restore robust behavioral rhythms to SCN-lesioned rats and hamsters (9,12,16), and cross-genotype grafting between clock mutant and wild-type animals has shown that restored rhythms are due to the presence of the donor pacemaker (21) The precise mechanisms by which SCN grafts restore function are still under investigation, but there is evidence for both neural efferents (18) and diffusible factors (24) as mediators of circadian clock function. In order to assess graft outgrowth and map the pattern of host innervation, markers must be used to identify the grafted tissue and its efferents.…”
Section: Introductionmentioning
confidence: 99%
“…In order to circumvent these limitations it is useful to take advantage of species-specific markers (3,26) or genetically modified cell lines and transgenic species (20,23). Again, there are disadvantages in that the species-specific marker may not be expressed in all regions of the donor brain including the SCN (24), and transgenic donors are not available for all animal models, such as the hamster and the rat. In addition, with the use of cross-species transplantation there is considerable risk for graft rejection requiring the use of immunosuppressive agents, such as Cyclosporin A, following grafting (6).…”
Section: Introductionmentioning
confidence: 99%